Volleyball technical skills as winning and qualification factors during the Olympic Games 2008 - Patsiaouras, A.; Moustakidis, A.; Charitonidis, K.; Kokaridas, D. (International Journal of Performance Analysis in Sport, 2010)
The purpose of this study was to examine the technical skills that emerged as statistically important for volleyball men teams' progress into the qualification round, semi-final and final in the Beijing Olympic Games of 2008. Collection of data included the use of the statistical recording program Data Volley 2 Professional (2005) for games evaluated. Additional statistical analyses included the use of SPSS 15.0. Kruskal-Wallis nonparametric test use revealed statistically significant differences among the teams concerning the "attack errors following bad receptions" factor. Additional statistical analyses using Mann - Whitney U test showed statistically important differences between the teams playing in each semi-final and the final with the qualification round teams regarding the "attack errors following bad receptions" factor. Statistically important differences were also noticed in the "attack after bad reception" between qualification round teams and teams playing in the final (Brazil- USA)